Initial Coin Offering (ICO): a systematic review of the literature - Moxotó, Ana Claudia (2021)
Initial ICO coin offerings have emerged as a new business financing mechanism. ICOs have raised more than $ 31.14 billion by 2019, sparking interest in finance studies. Despite ongoing scientific research on the topic, academic knowledge remains limited and fragmented. This study aims to conduct a systematic review of the literature with 30 contributions from journals published until January 2020. Based on an in-depth analysis of the publications identified, we describe the landscape of the field of ICOs focusing on two aspects. First, we conducted an analysis of the empirical articles that addressed the success determinants of ICOs. Second, we categorize relevant contributions in five different perspectives: human and social capital, technological characteristics, governance and legal aspects and financial details of the campaign. Thematic analysis was carried out to address dominant themes and subthemes in each perspective.